Dawn of desegregation J.A. De Laine and Briggs v. Elliott - Gona, Ophelia De Laine; ebrary, Inc. (Columbia : University of South Carolina Press, 2011)
"Though De Laine and the brave parents who filed Briggs v. Elliott initially lost their lawsuit in district court, the case grew in significance when the plaintiffs appealed the decision to the U.S. Supreme Court. Three years after the appeal, the Briggs case was one of the five lawsuits that shared the historic Brown decision. However, the ruling did not prevent De Laine and his family from suffering vicious reprisals from vindictive white citizens. In 1955, after he was shot at and his church was burned to the ground, De Laine prudently fled South Carolina in order to save his life. He died in exile in Charlotte, North Carolina, in 1974. Fifty years after the Supreme Court's decision, De Laine was awarded the Congressional Gold Medal in recognition of his role in reshaping the American civil rights landscape."--Book jacket.
Briars of discrimination -- Spokesman for the disenfranchised -- The challenge -- Ups and downs -- Transition -- June 8 -- Across the Rubicon -- An offer that was refused -- Warnings -- Showdown on Main -- A not-so-merry Christmas -- Liar, liar -- Moving on -- Federal District Court -- Verdicts -- New evil -- Armageddon.
Paperback edition published by the University of South Carolina Press, 2012.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Briggs, Harry, -- d. 1986 -- Trials, litigation, etc; Elliott, R. W. -- Trials, litigation, etc; DeLaine, Joseph A. -- 1898-1974.; Segregation in education -- Law and legislation -- South Carolina -- Clarendon County -- History -- 20th century; African Americans -- Civil rights -- South Carolina -- Clarendon County -- History -- 20th century; Civil rights movements -- South Carolina -- Clarendon County -- History -- 20th century; African American clergy -- South Carolina -- Clarendon County -- Biography; African American civil rights workers -- South Carolina -- Clarendon County -- Biography; Electronic books